2013
DOI: 10.12691/ajme-1-3-1
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Mechanics of Oscillating Mechanisms

Abstract: This paper extends a previous study on the mechanics of oscillating mechanisms in which motion of an object is produced by attached rotating eccentric masses. In addition to the well known twin contra-rotating pair (Dean drive), the single eccentric mechanism is studied. In contrast to the contra-rotating systems where the initially still object moves along a vertical track, this study shows that in case of a single eccentric mass the track of the same object is extended in both the horizontal and vertical dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Equations (7) to (9) contain friction forces, so the friction forces f iX , f iY and f iτ must be determined. We restrict ourselves to dry friction forces only and select the Stribeck friction model 13 as the friction model, which is given by where f s is the maximum static friction force; f d is the dynamic friction force. They are given by where μ s is the static friction coefficient; μ d is the dynamic friction coefficient; N is the normal support force of the horizontal plane to the support points; v is the relative velocity between the support point and the horizontal plane; v s and k are constants.…”
Section: Dynamics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Equations (7) to (9) contain friction forces, so the friction forces f iX , f iY and f iτ must be determined. We restrict ourselves to dry friction forces only and select the Stribeck friction model 13 as the friction model, which is given by where f s is the maximum static friction force; f d is the dynamic friction force. They are given by where μ s is the static friction coefficient; μ d is the dynamic friction coefficient; N is the normal support force of the horizontal plane to the support points; v is the relative velocity between the support point and the horizontal plane; v s and k are constants.…”
Section: Dynamics Analysismentioning
confidence: 99%
“…The former usually uses elastic brush structures, 7–10 which increase the difficulty of the motion modeling and control. In order to achieve two-dimensional motion, the latter usually needs two or more motors, 11–21 which limits the further simplification of the whole device structure. Moreover, additional software control algorithm is usually required to realize the coordination control of the motors; this increases the complexity of the program and the difficulty of the control of the rotation speed of motors.…”
Section: Introductionmentioning
confidence: 99%
“…There are generally two positions at which the inertial force becomes equal to the maximum static friction. Considering the normal force given by (13), both of them have to fulfill the nonlinear equation:…”
Section: B Cancelling the Maximum Static Frictionmentioning
confidence: 99%
“…Surprisingly, today relevant research continues and one can easily find Internet and press reports concerning claimed successful perpetual motion machines in Russia (see for example [11]); at the same time there are many relevant Internet articles referring to "pseudoscience". Although details for the technology applied are not available, in order to resolve confusion still existing, the detailed mechanics of Dean drive have been recently investigated for the vertical motion of an object [12,13], while its elastodynamics and equivalent electromagnetic analogues have been also studied [14]. The possibility of replacing rockets [15] through novel drives to achieve space propulsion (called "alternative propulsion"), seems to be a matter of scientific and technological prestige for many countries including China [16].…”
Section: Introductionmentioning
confidence: 99%
“…Handheld loads used in SBJ, whether ancient or modern, are designed to improve the jumping distance [ 5 , 6 , 7 , 8 , 9 ]. Campa et al [ 10 ] reported that the capacity of the explosive power of lower extremity was in correlation with the repeated-sprint ability (RSA) relate to jumping ability. Moreover, loading plyometric training has proven to be one of the more effective ways of improving sprinting and jumping performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%